Novel integrations of molten salt cavity tubular solar central receiver with existing gas-fuelled conventional steam power plants - Jamel M.S.; Abd Rahman A.; Shamsuddin A.H. (Taylor and Francis Ltd., 2023)
Air preheaters; Economizers; Electric power plants; Fused salts; Gas plants; Ionization of gases; MATLAB; Steam; Steam power plants; Central receivers; Feedwater; Heliostat field; Hybrid power plants; Integrated power; Pressure loss; Solar electric generating systems; Steam power cycle; Electric power system economics; Sugarcane Ramu stunt disease phytoplasma